ANALISIS KELEMBAGAAN KAWASAN STRATEGIS PARIWISATA NASIONAL (KSPN) DALAM PENYELENGGARAAN PENATAAN RUANG PROVINSI BALI - Ngakan Made Anom Wiryasa; Preantjaya W.P; Darma Warsika (JURNAL SPEKTRAN, 2018)
Institutional dynamics is very much in line with the economic dynamics in which there are many interactions. The dynamics of the institutional nature is due to the change of society's values and culture in accordance with current conditions and situations. The objectives of this research are: (i) to identify institutional sources related to Besakih-Gunung Agung Area and surrounding areas as KSPN in organizing spatial planning; (ii) identifying sources of conflict or disharmony in the arrangement of Besakih-Gunung Agung and surrounding areas after being designated as a National Tourism Strategic Area. (iii) make recommendations on the settlement of institutional conflicts in the management of the Besakih Area spatial arrangement. This study refers to empirical approaches (empirical approaches), because the research instrument tends to be designed to approach qualitative design. To obtain data and information from resource persons using semi-structured interviews. Conclusion: conflict of institutional sources: (i) Space / spatial Matra limitation; (ii) the limitations of the RTRW and no Zoning Rules yet. Recommendation: (i) to complete and socialize zonation regulations and / or Detail Plan for Besakih-Gunung Agung and surrounding areas; (ii) complement the RTRWP derivative relating to detail plan of Bali provincial strategic area (KSPN Pura Besakih-Gunung Agung and surrounding areas); (iii) existing institutional empowerment in the framework of orderly control of space and (iv) the development of tourism facilities based on the potential of nature tourism, culture, and especially religious or spiritual tourism. Keywords: institutional, RTRW (Spatial Plan), KSPN (National Tourism Strategic Area)